Impact of Free Shipping Promotion on E-Commerce Application Popularity in Indonesia - Saqina, Rahma Ta (International Journal of Education, Information Technology, and Others, 2024)
The rapid development of technology allows people to shop remotely through e-commerce applications. Because of a lot of e-commerce users in Indonesia, there is fierce competition for customers. One of his efforts for e-commerce companies is to offer free shipping promotions to users. On the other hand, among the various existing e-commerce applications, few are popular and widely adopted by Indonesian people. This study aims to know if the promotion of free shipping affects the popularity of e-commerce applications in Indonesia. The research methodology employed in this study was a qualitative research methodology and the data collection technique used in this study was an analysis of the literature, which collects and compares data from various literature sources. Results from this research show that free shipping promotions influence e-commerce applications' popularity in Indonesia. Other than free shipping promotions, Other factors affecting the popularity of e-commerce applications in Indonesia are the affordability of products., attractive special offers or discounts, diverse product selection, fast delivery, and attractive e-commerce display.